2018
DOI: 10.3390/colloids3010006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multimodal Silicas Using TG/DTG/DTA, Q-TG, and DSC Methods

Abstract: The formation of hierarchical, multimodal porosity materials with controlled shape and size of pores is the essential challenge in materials science. Properties of silica materials depend largely on different features: crystal structure, dispersity, surface composition, and porosity as well as the method of preparation and possible modification. In this paper, multimodal silicas obtained using different additives are presented. A-50 and A-380 aerosils and wide-porous SiO 2 milled at 300 rpm were used as the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The TG profile of MPS in Figure S5 (Supporting Information) exhibits weight loss upon heating due to H 2 O desorption (m/z = 18), corresponding to physically bound H 2 O and dehydration reactions between silanol groups (>200 °C) according to Equation 2. [38] In contrast, TMS-MPS shows little weight change from water loss upon heating (Figure 1b), which is in agreement with the FTIR results. In addition, the detected signal of m/z = 75 at temperatures exceeding 300 °C can be ascribed to a typical fragment of hydroxylated TMS, i.e., (CH 3 ) 2 Si-OH + ), as TMS groups on TMS-MPS can react with desorbed H 2 O (Equation 3) or remaining hydroxyl groups (Equation 4).…”
Section: Resultssupporting
confidence: 87%
“…The TG profile of MPS in Figure S5 (Supporting Information) exhibits weight loss upon heating due to H 2 O desorption (m/z = 18), corresponding to physically bound H 2 O and dehydration reactions between silanol groups (>200 °C) according to Equation 2. [38] In contrast, TMS-MPS shows little weight change from water loss upon heating (Figure 1b), which is in agreement with the FTIR results. In addition, the detected signal of m/z = 75 at temperatures exceeding 300 °C can be ascribed to a typical fragment of hydroxylated TMS, i.e., (CH 3 ) 2 Si-OH + ), as TMS groups on TMS-MPS can react with desorbed H 2 O (Equation 3) or remaining hydroxyl groups (Equation 4).…”
Section: Resultssupporting
confidence: 87%
“…Sautet et al 45 observed the effect of hydroxylation on the C Q value in their study of γ-alumina. The hydroxyl density of AAS is calculated by the thermal gravimetric analysis (TGA) of the samples using the Boer equation 46 (Supplementary Fig. 14 , Supplementary Table 4 ), and found to be within the range of 5.4 to 13 OH nm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates silica contains more physically bound water than SO 4 -SiO 2 and Cr/SO 4 -SiO 2 . The second step, in the range of 200-400°C corresponds to the release of vicinal silanol (bridging silanol) groups in the SiO 2 [45], the mass reduction of SiO 2 , SS 2-600, and Cr-SS 1 as much as 0.98%, 0.54%, and 0.34%, respectively. In the 400-900°C range, the third step corresponds to releasing geminal silanol groups in the SiO 2 [46].…”
Section: Thermal Stability Of the Catalystsmentioning
confidence: 99%